Media as A Public Relations Tool: Analyzing Its Impact on Brand Image of Access Bank Plc - Ifeanyi C. Ehule (INTERNATIONAL JOURNAL OF MARKETING AND COMMUNICATION STUDIES, 2026)
This study examined the role of public relations in raising awareness about child labour in Rivers State using Access Bank Plc as a case study. The objectives were to determine employees’ perception of the effectiveness of the bank’s public relations strategies in creating awareness, to assess the role of media exposure in shaping employees’ attitudes toward the campaign, and to evaluate the extent to which the campaigns contribute to addressing child labour issues. The study was anchored on the agenda-Setting Theory (McCombs & Shaw, 1972), the Two-Way Symmetrical Model of Public Relations (Grunig & Hunt, 1984), and the Technological Determinism Theory (McLuhan, 1964). A survey research design was employed with a population of 112 employees across four Access Bank branches in Port Harcourt, from which a sample size of 88 respondents was determined using Taro Yamane’s formula at a 5% margin of error. Data were collected using structured questionnaires and analyzed with descriptive statistics. Findings revealed that employees considered the bank’s strategies effective in creating awareness, with media exposure positively shaping attitudes and reinforcing messages, while campaigns were also perceived as contributing meaningfully to reducing child labour through sensitization, stakeholder engagement, and influencing policy discussions. The study concludes that Access Bank’s public relations strategies align with agenda-setting, two-way communication, and technological determinism, making them effective tools for both awareness and social change. It recommends sustaining and intensifying media campaigns, expanding community dialogue, fostering collaborations with government and NGOs, and instituting monitoring mechanisms to measure long-term impact.